PENGEMBANGAN MODUL PEMBELAJARAN TEMATIK PERISTIWA KEBANGSAAN MASA PENJAJAHAN UNTUK KELAS V SEKOLAH DASAR - Anggraini, Susi; Mering, Aloysius; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research aims to determine the design of thematic learning modules, thematic learning module profiles, and learning outcomes on thematic learning of colonialism national events used modules in grade V elementry schools. This research is a development research use 4D model with 4 stages consist of define, design, develop, and disseminate. The results showed the development of thematic modules used range of 0-4 obtained an average value by material experts, media experts, and design experts are 3.58 with valid criteria. Student responses to thematic modules obtained an average 3.31 with valid criteria. The thematic module profile includes introduction, content and evaluation section and fulfilled the characteristics of self instruction, self contained, adaptive and user friendly. Learning outcomes of students cognitive aspects use thematic modules obtained percentage of completeness is 88%. Learning outcomes of student attitudes and skills aspect after use thematic learning modules are included good categories.Keywords: Thematic module, National events of colonialism, 4D Model.